Best Answer

We can rewrite this as 2x2 -6x-1=0

Now if you want to solve this, you can use the quadratic equation.

a=2

b=-6

c=-1

So x= [6+ or - ( square root of (36+8) ]/ 4

= [6+ or - (2square root of (11))/]4

Q: 2x squared -1 equals 6x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x(2x + 1)

(2x-4)(x-1) = 0

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)

Related questions

3x(2x + 1)

(2x-4)(x-1) = 0

3(2x - 1)(x - 2)

6x^2 + 11x + 4 is a Quadratic Statement. It is NOT an equation, because there is no 'equals' (=). It will factor to ( 3x + 4)(2x + 1)

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

4x3+10x2-6x 2x(2x2+5x-3) 2x(2x-1)(x+3)

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

(2x - 1)(6x + 5)

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

6x + 3 = 2x + 5 4x = 2 x=1/2

If: y = 5x^2 -2x +1 and y = 6 -3x -x^2Then: 5x^2 -2x +1 = 6 -3x -x^2Transposing terms: 6x^2 +x -5 = 0Factorizing: (6x -5)(x +1) = 0 => x = -1 or x = 5/6Through substitution points of intersect are at: (-1, 8) and (5/6, 101/36)